Positivity of Demodex spp. in biopsy specimens of nevi - Sener, Serpil; Karaman, Ulku; Colak, Cemil; Aydin, Nasuhi Engin; Sasmaz, Sezai; Iraz, Meryem (Malaysian Soc Parasitology Tropical Medicine, 2009)
Melanocytic skin tumors are caused by nevus cells, epidermal melanocytes and dermal melanocytes. The aim of the study was to detect the positivity of Demodex spp. in biopsy specimens of skin diagnosed as nevus. In this retrospective study, the specimens obtained from 110 patients diagnosed with nevus and stained by hematoxylin & eosin (H&E) method were assessed for Demodex. Statistical analysis was done using independent sample t test, Pearson Chi-square and Yates' adjusted Chi-square test. For statistics, p<0.05 was considered significant. Consequently, 43 (39.1%) out of 110 specimens were detected to have Demodex spp. Demodex colonization augmented in nevi can be explained by the possible affinity of the parasite to the melanin pigment.
Keywords: Folliculorum; Demodicidosis; Rosacea; Risk